2015
DOI: 10.1111/flan.12125
|View full text |Cite
|
Sign up to set email alerts
|

Strategy and Action: Assessing Student‐Led Culture Workshops Within the Professions

Abstract: In order to prepare students to successfully engage with native speakers and members of heritage language communities both at home and abroad, educators must develop course curricula that emphasize cultural practices, products, perspectives, and comparisons as well as provide students with opportunities to directly apply the skills that they have acquired in the classroom across a range of other settings. This article describes a Culture for the Professions course whose curriculum was based on the four steps o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…In fact, Pellettieri () reported that, prior to participating in SL, 39% of her students had never spoken Spanish to a native speaker (p. 294). Two recent, notable studies described previously unexplored applications of SL: Carracelas‐Juncal () examined the positive impact of SL in graduate‐level, online courses for teacher education on students who were heritage speakers of Spanish, and King de Ramírez () reported on a Culture for the Professions course whose curriculum was designed around three pedagogies: the cultural intelligence model, community SL, and Language for Specific Purposes.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In fact, Pellettieri () reported that, prior to participating in SL, 39% of her students had never spoken Spanish to a native speaker (p. 294). Two recent, notable studies described previously unexplored applications of SL: Carracelas‐Juncal () examined the positive impact of SL in graduate‐level, online courses for teacher education on students who were heritage speakers of Spanish, and King de Ramírez () reported on a Culture for the Professions course whose curriculum was designed around three pedagogies: the cultural intelligence model, community SL, and Language for Specific Purposes.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In these cases, race appeared as a demographic variable in a list alongside other variables such as age and gender. Articles referenced race to describe the racial makeup of participants (e.g., King de Ramírez, 2015) and schools (e.g., Ee, 2017) and to measure race in research instruments (surveys, questionnaires; e.g., Ducate et al, 2011). Race appeared in empirical analyses as a demographic variable that was controlled for in studies with no effect (e.g., Bassman & Ironsmith, 1986; Kleinsasser, 1992) or as a variable that was not controlled for due to reasons such as a small sample size (e.g., Fukuda & Nishikawa Chávez, 2021) or because the data were not available (e.g., Surface & Dierdorff, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Tablo 6). Diğer yandan, yurtdışı deneyimi ve yurtdışı çalışma niyeti (Remhof vd., 2013) (Deng & Gibson, 2009), kültürel farklılık (De Ramirez, 2015 ;Gregory, Prifling & Beck, 2009;Kaufman & HwAng, 2015), farklılıkların yönetimine (Yeşil, 2009), hedef oryantasyonu öyküleme (Gertsen & Soderberg, 2010), yabancıların başarısı (Lee, 2010), işletmenin ana rekabat kaynakları (Capatina vd., 2011), kültürlerarası liderlik (Ersoy, 2014), uluslararası deneyim (Ott & Michailova, 2018;Ott & Ishakova, 2019) (Şahin & Gürbüz, 2014 (Arastaman, 2018;İlhan & Çetin, 2014a;Şahin vd., 2013a). İlişkisel inceleme sonuçları ise KZ'nın, Kültürlerarası Etkinlik (Guðmundsdóttir, 2015;Huff vd., 2014;Lin vd., 2012;Shu vd., 2017;Zhang & Oczkowski, 2016), Performans (Görev performansı, iş performansı, lider performansı, takım performansı) (Groves & Feyerherm, 2011;Jyoti & Kour, 2015;Malek & Budwar, 2013;Presbitero, 2016a;Presbitero & Toledano, 2018;Şahin & Gürbüz, 2012;Wang, 2016, Wang vd.…”
Section: Doğan and Uysal | 155unclassified